P-40 ASSOCIATION BETWEEN LIVER STIFFNESS MEASUREMENTS USING MR ELASTOGRAPHY AND PORTOSYSTEMIC SHUNTS IN PATIENTS WITH ADVANCED CHRONIC LIVER DISEASE - Rodrigo Pereira Luz Pereira; Cristiane Nogueira Villela; Juliana Mesiano; Guilherme Cunha Moura (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Spontaneous portosystemic shunts (SPSSs) have been reported in 60% of cirrhotic patients and its prevalence increases with the deterioration of liver function. SPSSs are often associated with hepatic encephalopathy, gastroesophageal varices and increased risk for complications and death. Therefore, the selection of patients with a high probability of having significant SPSSs can have great impact in the management of patients with liver cirrhosis. In cirrhotic patients, liver stiffness measurements show a good correlation with the severity of disease and the occurrence of gastroesophageal varices. We hypothesize that liver stiffness values could also correlate well or even predict the presence of significant portosystemic shunts. Patients / Materials and Methods: This was a retrospective study of 51 patients with advanced chronic liver disease/cirrhosis who underwent liver magnetic resonance imaging with elastography (MRE) from 2022 to 2023. MR images were reviewed by two radiologists looking for the presence of SPSSs, defined as spontaneous communications between the portal venous system and/or splanchnic veins and the systemic venous system. In addition, presence or absence of gastroesophageal varices was also recorded. Regarding SPSSs, patients were assigned into two groups: with and without SPSSs. Among patients with SPSSs patients were assigned into two groups: Large SPSSs (L-SPSSs, ≥8 mm), small SPSSs (S-SPSSs <8mm), or without SPSSsMedian. Levels of MRE between patients with and without SPSSs was analyzed and the accuracy of liver stiffness by MRE to predict SPSSs was evaluated by AUROC curves. A statistical significance level of 0.05 was adopted. Results and Discussion: Among 51 included patients, 68% were male, and mean age was 64 years old. SPSSs were present in 28% of patients with only 6.5% having LSPSSs. Gastroesophageal varices were identified in 32%. Mean liver MRE stiffness values was 4.4 kPa (3.0 – 13.1 kPa). The performance of MRE for the prediction of SPSSs and gastresophageal varices was good, with an AUROC of 0.85 (0.75 – 0.97; p< 0.001) for SPSSs and 0.84 (0.72 – 0.96; p<0.001) for Gastroesophageal varices. The best MRE elastography cutoff for the presence of SPSSs and gastroesophageal varices was 5.0 kPa (S=85%, Sp=83%,PPV=61% and NPV=93%) and for the detection of gastroesophageal varices was 4.4 KPa (S=83%,Sp=77%, PPV=66% and NPV=91%). Conclusions: MRE elastography is a reliable tool to adequately exclude non-invasively the presence of portosystemic shunts and gastresophageal varices and help identify patients at low risk for the development of related complications.